Atrioventricular junction ablation in patients with atrial fibrillation treated with cardiac resynchronization therapy: positive impact on ventricular arrhythmias, implantable cardioverter‐defibrillator therapies and hospitalizations. (18th December 2017) - Gasparini, Maurizio; Kloppe, Axel; Lunati, Maurizio; Anselme, Frédéric; Landolina, Maurizio; Martinez‐Ferrer, Jose Bautista; Proclemer, Alessandro; Morani, Giovanni; Biffi, Mauro; Ricci, Renato; Rordorf, Roberto; Mangoni, Lorenza; et al.
Abstract : Aims: We sought to determine whether atrioventricular junction ablation (AVJA) in patients with cardiac resynchronization therapy (CRT) implantable cardioverter‐defibrillator (ICD) and with permanent atrial fibrillation (AF) has a positive impact on ICD shocks and hospitalizations compared with rate‐slowing drugs. Methods and results: This is a pooled analysis of data from 179 international centres participating in two randomized trials and one prospective observational research. The co‐primary endpoints were all‐cause ICD shocks and all‐cause hospitalizations. Out of 3358 CRT‐ICD patients (2720 male, 66.6 years), 2694 (80%) were in sinus rhythm (SR) and 664 (20%) had permanent AF—262 (8%) treated with AVJA (AF + AVJA) and 402 (12%) treated with rate‐slowing drugs (AF + Drugs). Median follow‐up was 18 months. The mean (95% confidence intervals) annual rate of all‐cause ICD shocks per 100 patient years was 8.0 (5.3–11.9) in AF + AVJA, 43.6 (37.7–50.4) in AF + Drugs, and 34.4 (32.5–36.5) in SR patients, resulting in incidence rate ratio (IRR) reductions of 0.18 (0.10–0.32) for AF + AVJA vs. AF + Drugs ( P  < 0.001) and 0.48 (0.35–0.66) for AF + AVJA vs. SR ( P  < 0.001). These reductions were driven by significant reductions in both appropriate ICD shocks [IRR 0.23 (0.13–0.40), P  < 0.001, vs. AF + Drugs] and inappropriate ICD shocks [IRR 0.09 (0.04–0.21), P  < 0.001, vs. AF + Drugs]. Annual rate of all‐cause hospitalizations was significantly lower in AF + AVJA vs. AF + Drugs [IRR 0.57 (0.41–0.79), P  < 0.001] and SR [IRR 0.85 (073–0.98), P  = 0.027]. Conclusion: In AF patients treated with CRT, AVJA results in a lower incidence and burden of all‐cause, appropriate and inappropriate ICD shocks, as well as to fewer all‐cause and heart failure hospitalizations. Clinical Trial Registration: NCT00147290, NCT00617175, NCT01007474.